Bioinspired Functional Black Phosphorus Electrospun Fibers Achieving Recruitment and Biomineralization for Staged Bone Regeneration. Issue 50 (23rd November 2020) - Cheng, Liang; Chen, Zhijie; Cai, Zhengwei; Zhao, Jingwen; Lu, Min; Liang, Jing; Wang, Fei; Qi, Jin; Cui, Wenguo; Deng, Lianfu
Abstract: The ideal bone repair material should firstly recognize and recruit osteoblast precursor cells to initiate the repair process, then promote the differentiation of osteoblasts and accelerate the mineralization of the extracellular matrix (ECM). Here, a bioinspired staged bone regeneration strategy which loads bone morphogenetic protein2 (BMP2 )‐modified black phosphorus (BP@BMP2 ) nanosheets to a polylactic acid (PLLA) electrospun fibrous scaffold, with a combination of recruiting osteoblast precursor cells and biomineralization properties for bone regeneration, is constructed successfully by micro‐sol electrospinning technique. BP, acting as carriers, can not only provide a negative surface and a strong BMP2 loading ability but can also promote biomineralization in a 3D manner on the electrospun fibrous scaffold, while the BMP2 is to target osteoblast precursor cells for recruitment and osteogenesis differentiation, which endows BP@BMP2 nanosheets with staged bone regeneration ability. Furthermore, the in vitro and in vivo data showed that the BP@BMP2 loaded electrospun fibrous scaffold have good biocompatibility and a strong osteogenesis ability resulting in rapid new bone tissue regeneration. Altogether, this newly developed bioinspired BMP2 ‐modified BP electrospun fiber with staged bone regeneration properties via recruiting osteoblast precursor cells to the bone injured site and accelerating biomineralization can be a promising approach in physiologic bone repair. Abstract : A bioinspired bone morphogenetic protein2 (BMP2 )‐modified black phosphorus (BP) electrospun fiber with staged bone regeneration properties via recruiting osteoblast precursor cells to the bone injured site and accelerating biomineralization are developed for effectively promoting critical cranial defect physiological regeneration. BP could not only provide a negative surface and a strong BMP2 loading ability but also promote biomineralization in electrospun fibrous scaffold.